Holocene Vegetation, Climate, and Carbon History on Western Kodiak Island, Alaska - Peteet, Dorothy M.; Nichols, Jonathan E.; Mann, Daniel H. (Frontiers in Earth Science, 2019)
At Phalarope Pond, western Kodiak Island, a multidisciplinary study using pollen and spores, macrofossils, stable isotopes, and carbon accumulation provides the Holocene vegetation and climate history following the deglaciation that began over 16,000 cal years ago (yr BP). Following a cold and dry Younger Dryas, a warm and wet early Holocene was characterized by abundant ferns in a sedge tundra environment with maximum carbon accumulation, similar to high latitude peatlands globally. About 8,700 cal yr BP sedge and ferns declined and climate remained warm as drier conditions prevailed, limiting carbon sequestration. The abrupt shift in D/H isotopes of about 60% indicates a shift to cooler conditions or a more distal moisture source. Neoglaciation beginning about 3,700 cal yr BP is evident from increases in Artemisia, Empetrum and Betula, signifying cooler conditions, while Alnus declines, paralleling regional trends.